Water salinity during masculinization of Nile tilapia in biofloc system - Do Valle, Rafael Cavaca Alves (2024)
The objective of this work was to evaluate the effect of different water salinity levels on the growth performance, survival, and masculinization rate of Nile tilapia (Oreochromis niloticus) larvae in a biofloc technology (BFT) system. Seven salinity levels (0, 2, 4, 6, 8, 10, and 12 g L-1) were tested during four weeks in the masculinization period after the absorption of the yolk sac in a matured biofloc system. The water quality variables were within the recommended range for Nile tilapia farming. However, the nitrite peaks were higher at higher salinity levels and were associated with the lower survival of fish at salinity levels equal to or higher than 6 g L-1. There was no difference between treatments for average final body weight and masculinization rate. Final biomass and survival decreased, and the feed offered as a proportion of final biomass showed the worst results because of the increase in salinity. Therefore, since higher masculinization rates are not obtained at slight and moderate levels of saline water, salinity should be kept close to 0 g L-1 for the masculinization protocol of Nile tilapia in a BFT, for a better survival and higher biomass of the fish, as well as a lower waste of the offered feed.